(untitled) (Argos, 2025)
This work will analyze Greek paintings of daily life activities, in this case, fetching water from the Athenian communal fountain during the last three decades of the fifth century B.C. We shall look for the connection between images painted in ceramic utensils and their counterpart in political, artistic, and economical activities during the Peisistratic era. The iconography of vases depicting women in the fountain house might be understood as a representation of the prosperous and intellectually stimulating atmosphere at the polis such as it was encouraged by Peisistratos and his sons.